Design of step grate firing by utilizing palm empty-fruit-bunch fuel for industrial steam boiler construction - Supphachai Srasri; Niran Bhudsarakam; Pornchai Limsutthiphong; Tanapat Ratanapitag; Amphawan Julsereewong (Energy Reports, 2021)
To achieve desired performance of steam boiler and low emission of hazardous air pollutants for generating electric power from palm oil industry, combustion characteristics of grate firing should be optimal for difficult biomass fuels. This article aims to present a design of step grate firing with high thermal efficiency for combustion of selected palm empty fruit bunch (EFB) fuel with moisture content of 38.4% and ash content of 3.39%. The proposed grate firing is not only specially designed for continuous 3-month operation but also particularly suited to construction of an industrial boiler rated at 80 tons/h, 45 bar, and 430 °C. The reciprocating step grate as well as air distribution for optimized combustion characteristics is specified based on computational fluid dynamics (CFD) analysis and practical experience. The required boiler can be successfully constructed and smoothly operated by installing the designed step grate firing as part of a whole system at a biomass power plant in Thailand.
Keywords: Thermochemical Biomass Conversion Processes; Biofuel production and bioconversion; Photovoltaic System Optimization Techniques